1969
DOI: 10.1113/jphysiol.1969.sp008863
|View full text |Cite
|
Sign up to set email alerts
|

The responses of cortical neurones to monoamines under differing anaesthetic conditions

Abstract: SUMMARY1. Noradrenaline, isoprenaline, 5-hydroxytryptamine and acetylcholine have been applied into the environment of single neurones in the cat cerebral cortex by micro-iontophoresis. The influence of anaesthesia on the neuronal responses to these drugs was studied.2. In general, excitation of neurones by noradrenaline occurred commonly in both unanaesthetized encephale isole (48 %) and N20-halothane anaesthetized preparations (57 %) while depressions were less frequent (24 and 20 % respectively). The pictur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

1970
1970
2007
2007

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(17 citation statements)
references
References 26 publications
2
15
0
Order By: Relevance
“…Lipski (1981) in a review of antidromic invasion of motoneurones and other cells, concluded that the technique was of value. This leaves the possibility that the barbiturate anaesthesia used by Engberg et al (1979) significantly affected the response of motoneurones to 5-HT in much the same way as barbiturates affect the responses of cortical neurones to 5-HT (Johnson et al, 1969).…”
Section: Discussionmentioning
confidence: 99%
“…Lipski (1981) in a review of antidromic invasion of motoneurones and other cells, concluded that the technique was of value. This leaves the possibility that the barbiturate anaesthesia used by Engberg et al (1979) significantly affected the response of motoneurones to 5-HT in much the same way as barbiturates affect the responses of cortical neurones to 5-HT (Johnson et al, 1969).…”
Section: Discussionmentioning
confidence: 99%
“…Details of the techniques used for the extracellular iontophoresis of drugs onto spontaneously firing neurones in the cat posterior sigmoid gyrus have been presented elsewhere (Roberts & Straughan, 1967;Johnson, Roberts & Straughan, 1969b). Anaesthesia was induced by N20-halothane and was maintained either on 75% nitrous oxide in oxygen and 10% halothane, or on intravenous pentobarbitone sodium (25 mg initially, supplemented as necessary).…”
Section: Methodsmentioning
confidence: 99%
“…Barbiturate anaesthetized cats were used in experiments with 5-HT to achieve mainly depressant responses (Johnson et al, 1969b) The following drugs were used in aqueous solution in the micropipettes: Glycine and y-aminobutyric acid (GABA) 0-2 M, acidified to pH 3-5 with HCl; 5-hydroxytryptamine hydrogen maleate (5-HT) 0-2 M, pH 3 5; acetylcholine chloride (ACh) 0-2 M, pH 3 5-4 0 and strychnine sulphate 0-01 M, pH 4 0.…”
Section: Methodsmentioning
confidence: 99%
“…The opposite effects of noradrenaline were not due to injection at different sites since these were frequently indistinguishable from subsequent inspection of cannulae positions. It is possible that the depth of anaesthesia determined the direction of the response to noradrenaline, a possibility that is consistant with the finding that responses of cortical neurones to iontophoretic application of monoamines (but not acetylcholine) were modified by the depth of anaesthesia (Johnson, Roberts & Straughan, 1969). This work was supported by a grant from the Wellcome Trust.…”
Section: Discussionmentioning
confidence: 93%